AN ANALYTICAL METHOD FOR DETERMINING SNOW CAPACITYOF SNOW PROTECTION MEANS ON HIGHWAYS IN THE MOUNTAINOUS AREA - Бєлятинський, А.; Угненко, Є.; Тимченко, О. (Proceedings of National Aviation University (archive), 2012)
The article investigates the problem of snow capacity of protective means. The aim of the article is to determine snow capacity of snow protection means on highways in mountainous areas. To carry out theoretical research, analytical methods were used